High Resolution Computed Tomography chest findings among people affected by corona virus disease in a tertiary hospital of Nepal - Kayastha, Rumita; Acharya, Riwaz; Pradhan, Sunil; Tuladhar, Abhushan Siddhi; Shrestha, Amit (Nepal Medical College Journal, 2023)
Clinical assessment, chest X-ray (CXR) and chest high-resolution computed tomography (HRCT) are used in the management of Corona virus disease-19 (COVID-19). This retrospective cross sectional study included 251 patients admitted to Nepal Medical College Teaching Hospital (NMCTH) with a diagnosis of COVID‑19 infection confirmed by Reverse Transcriptase- Polymerase Chain Reaction (RT‑PCR). These patients underwent chest HRCT within the first two weeks of hospital admission. Images were evaluated for various HRCT findings & semi- quantitative CT Severity Score (CT –SS) was calculated based on the extent of lobar involvement. Out of 251 patients with positive RT PCR test, 127 were male (50.6%) and 124 female (49.4%). Typical bilateral peripheral subpleural ground glass opacities were demonstrated in 98.8% of patients; followed by thoracic lymphadenopathy (80.8%), interlobular septal thickening (80.4%),vascular changes (44.2%), focal consolidation (28.6%), consolidation with ground glass opacity (15%), pleural effusion (13.1%) bronchiectasis (3.8%), fibrotic changes (3.1%) and reversed halo pattern (0.7%). Calculated CT- SS showed moderate score in 130 patients (51.7%) followed by severe score in 67 patients (26.6%) and mild score in 51 patients (20.3%). HRCT can be used as a one stop radiological investigation for the diagnosis and prognosis of corona virus disease and CT -SS might be beneficial for diagnostic workflow in symptomatic cases.